Environment-friendly external wall thermal insulation porous material and preparation method thereof

By using the combination of flame retardant pore composite, gasification flying -ash base, and other components, the problem of poor stability of the fibrin gas gel stability was solved, and the thermal insulation performance and durability of the material were significantly improved.

CN119371155AActive Publication Date: 2025-01-28SUZHOU LOUCHENG NEW MATERIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411948144.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-01-28
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The stability of cellulose aerogel is poor, and it is prone to structural collapse, affecting the insulation performance of the material.

Method used

Use flame retardant pore composite, gasification fly ash base mass polymer fillers, nano cellulose, methyl trimethyloxylsilite and polyethylene alcohol, etc., to modify the gas gel through the solution, increase its structural stability The pore complexity.

Benefits of technology

It significantly enhances the thermal insulation performance of the material, has waterproof and fire resistance, and improves the applicability, safety and durability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371155A_ABST
    Figure CN119371155A_ABST
Patent Text Reader

Abstract

The invention discloses an environment-friendly external wall thermal insulation porous material and a preparation method thereof, and relates to the technical field of thermal insulation materials. The environment-friendly external wall thermal insulation porous material is prepared from a flame-retardant pore-forming compound, gasified fly ash-based geopolymer filler, nano cellulose, methyltrimethoxysilane and polyvinyl alcohol, a flame-retardant pore-forming compound and methyltrimethoxysilane are modified by adopting a solution method to obtain a multi-dimensional pore modified aerogel solution, and then a gasified fly ash-based geopolymer filler is used for further filling a pore structure of aerogel, so that not only is the stability of the aerogel structure increased, but also the complexity of pores is increased, and the flame-retardant property of the aerogel is improved. According to the present invention, the porous structure of the material has characteristics of porosity, multi-dimensional property and multi-layer property so as to significantly enhance the thermal insulation property, further has certain hydrophobic and flame retardant properties, can provide the waterproof and fireproof effects, and can enhance the applicability and the durability of the exterior wall material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heat insulation materials, and specifically refers to an environmentally friendly exterior wall thermal insulation porous material and a preparation method thereof. Background Art

[0002] External wall insulation technology is one of the important means of building energy conservation. The performance and configuration of insulation materials will directly affect the insulation effect of the exterior wall. In the traditional thermal insulation industry, common thermal insulation materials, such as polyurethane and expanded polystyrene, are derived from non-renewable fossil raw materials. Therefore, it is urgent to seek environmentally friendly and sustainable thermal insulation materials.

[0003] Aerogel materials have a unique three-dimensional porous structure, showing the characteristics of low density, high porosity and low thermal conductivity, and have become an ideal substitute for traditional petroleum-based foam insulation materials; cellulose not only has the characteristics of good biocompatibility, renewable, degradable, economical and non-toxic, but also has the advantages of high corrosion resistance, high strength and high modulus. Therefore, cellulose aerogel, as the representative of the third generation of biomass aerogel, not only inherits the advantages of traditional aerogels with large specific surface area and high porosity, but also overcomes the shortcomings of poor mechanical properties of inorganic aerogels, cumbersome preparation steps of organic aerogels and non-degradability. As a new type of green material, cellulose aerogel not only shows great potential in thermal insulation applications, but also better meets the requirements of sustainable development, providing a new solution for reducing global energy consumption.

[0004] The existing technology currently has the following problems:

[0005] Cellulose aerogel has poor stability and is prone to structural collapse, which in turn has an adverse effect on the thermal insulation properties of the material. Summary of the invention

[0006] In view of the above situation, in order to overcome the defects of the prior art, the present invention proposes an environmentally friendly exterior wall insulation porous material, comprising the following components in parts by weight: 10-20 parts of flame retardant pore-forming composite, 30-40 parts of gasified fly ash-based geopolymer filler, 4-5 parts of nanocellulose, 8-10 parts of methyltrimethoxysilane, and 8-10 parts of polyvinyl alcohol.

[0007] The flame-retardant pore-forming composite comprises the following components in parts by weight: 10-20 parts of phosphorus-doped graphite-like nitrogen oxide and 30-40 parts of ZIF-8 zeolite imidazole framework material.

[0008] The gasified fly ash-based geopolymer filler is a thermal insulation filler obtained by synergistically modifying the gasified fly ash as a raw material, calcining and activating the material, using sodium hydroxide, sodium silicate and deionized water to prepare an alkali activator, mixing and stirring the activated material, the alkali activator, a hydrogen peroxide foaming agent and an oleic acid foam stabilizer.

[0009] The method for preparing the flame-retardant pore-forming composite specifically comprises the following steps:

[0010] (1) Urea and diammonium hydrogen phosphate are added to 200-300 mL of deionized water, the amount of urea added is 5.0 g, and magnetic stirring is performed for 3-4 hours at a stirring speed of 500-600 rpm to completely dissolve the urea. The clarified solution is placed in a refrigerator at -18°C for 10-12 hours, and then freeze-dried to remove moisture. The solution is ground into powder and added to a sealed ceramic crucible. The solution is then calcined in a muffle furnace at 500-550°C for 3-4 hours, and the heating time is controlled within 100 minutes. The yellow product is collected and ground. The phosphorus atom doping replaces the carbon sites in the graphite-like nitrogen oxide skeleton, and the basic morphology of the graphite-like nitrogen oxide is not destroyed. However, after phosphorus doping, the two-dimensional layered structure presents micron-sized wrinkles, and the nanosheets are larger and more obvious, thereby obtaining phosphorus-doped graphite-like nitrogen oxide;

[0011] (2) 80-100 mg of zinc nitrate hexahydrate and the phosphorus-doped graphite-like nitrogen oxide described in step (1) are poured into a methanol solution, ultrasonically dispersed to form a uniform dispersion, and then the dispersion is poured into 10 mL of a methanol solution of 2-methylimidazole, wherein the methanol solution of 2-methylimidazole contains 1.0-1.2 g of 2-methylimidazole, stirred at room temperature for 2 hours, and then allowed to stand for precipitation, filtered, washed, and dried to form a ZIF-8 zeolite imidazole framework material with zinc nitrate hexahydrate and 2-methylimidazole. The ZIF-8 particles are uniformly distributed on the surface of the phosphorus-doped graphite-like nitrogen oxide and tightly combined to obtain a flame-retardant pore-forming composite, which not only reduces the agglomeration of the ZIF-8 particles, but also facilitates the uniformity and multi-level pore-forming of the subsequent cross-linking reaction. In addition, the porous protective film of the composite itself also has certain flame retardant and waterproof properties, which is beneficial to the safety and durability of the exterior wall building materials.

[0012] Preferably, in step (1), the amount of diammonium hydrogen phosphate added is 0.3-0.5 g. The addition of diammonium hydrogen phosphate provides phosphorus, which is beneficial to improving the flame retardant and water-resistant properties of graphite-like nitrogen oxide;

[0013] Preferably, in step (2), the content of zinc atoms in the flame retardant pore-forming composite is 5.4-6.8%. The presence of zinc element has a good smoke suppression effect and can be combined with phosphorus and nitrogen elements to exert more excellent flame retardant properties. At the same time, zinc element can form an oxide protective film on the surface of the material, thereby having good waterproof properties.

[0014] The method for preparing the gasified fly ash-based geopolymer filler specifically comprises the following steps:

[0015] a. Put the gasified fly ash into a muffle furnace at 700-800℃ and calcine until the mass no longer changes. Grind it. There are a lot of glass beads on the surface of the gasified fly ash particles. The main components are silicon dioxide and aluminum oxide. Under the action of high temperature, the originally stable and orderly structure is destroyed, and more amorphous monomers are generated, which is conducive to the alkali excitation reaction of the gasified fly ash and the leaching of silicon and aluminum elements in the fly ash, so as to prepare a polymer with higher strength, more uniformity and density, and obtain a calcined activated material;

[0016] b. Mix sodium hydroxide, sodium silicate and 25 mL of deionized water and stir evenly. The amount of sodium hydroxide added is 2.0 g. Then weigh 30.0 g of the obtained alkali activator and the calcined activation material described in step a and mix and stir. Add 0.6-0.7 g of oleic acid foam stabilizer and 0.6-0.7 g of hydrogen peroxide foaming agent. Stir rapidly for 1-2 min at a stirring speed of 800-1000 rpm and a shear rate of 8000-10000 rpm. Then pour the slurry into a mold and put it into a 60°C standard curing box for curing for 3 days. Under the action of sodium hydroxide, The Si-O and Al-O covalent bonds in the gasification fly ash are broken, and the reorganization and polycondensation form a polysilicon-aluminum compound with a bonded network structure based on -SiO4-AlO4, which can increase the compressive strength of the polymer and form a large number of closed pores inside the geopolymer, effectively improving the porosity and enhancing the thermal insulation performance. Therefore, the process method is used to modify the gasification fly ash to prepare a geopolymer thermal insulation material with fire resistance, high temperature resistance and high pressure resistance, which improves the current situation that organic thermal insulation materials are easy to age and inorganic materials have poor thermal insulation, and obtains a gasification fly ash-based geopolymer filler;

[0017] Preferably, in step b, the amount of sodium silicate added is 5.5-6.5 g. Sodium silicate can effectively adjust the silicon-aluminum ratio in the reaction system, thereby facilitating the formation of uniform and stable bubble pores with good thermal insulation performance.

[0018] The present invention also provides a method for preparing an environmentally friendly exterior wall thermal insulation porous material, which specifically comprises the following steps:

[0019] S1. Add 0.8-1.0g of nanocellulose to 100mL of deionized water, then add 1.6-2.0g of polyvinyl alcohol, and stir magnetically at room temperature for 24h. Add methyltrimethoxysilane liquid to the mixture of polyvinyl alcohol and nanocellulose, stir to make it evenly dispersed, then add the flame-retardant pore-forming composite, and stir magnetically for 1-2h. Under the further cross-linking action of the flame-retardant pore-forming composite, the network structure of the aerogel is more dense, and the pore-forming uniformity and multi-level are significantly enhanced, which can effectively capture and store energy and enhance the thermal insulation performance. In addition, the incorporation of phosphorus, nitrogen, and zinc elements in the flame-retardant pore-forming composite improves the flame retardancy and waterproof properties of the aerogel, thereby obtaining a multidimensional pore-modified aerogel solution.

[0020] S2, pouring the multidimensional pore modified aerogel solution described in step S1 into a silica gel mold, pre-freezing it in a refrigerator at 4°C for 1-2h, adding the gasified fly ash-based geopolymer filler and stirring it, and then ultrasonically treating it for 1-2h, with an ultrasonic temperature of 5-6°C and an ultrasonic power of 600-800W, so that the gasified fly ash-based geopolymer filler can fully enter the pores of the aerogel and further fill the pore structure of the aerogel, providing the aerogel with abundant mesopores and increasing the complexity of the pores, so that the micron-scale pore structure has porosity. , multidimensionality and multi-levelness, thus significantly enhancing the thermal insulation performance, waterproof performance and flame retardant performance. The mesh bonding structure of the gasified fly ash-based geopolymer filler also enhances the compressive strength of the aerogel, and can be used as a stabilizer to reduce the collapse of the pores in the aerogel, which is conducive to better exerting the thermal insulation, waterproof and fireproof properties, and improving the durability of the material. Then, it is vacuum freeze-dried at -70°C for 24-48h, and the obtained aerogel is placed in an oven at 70-80°C for 3-4h to obtain an environmentally friendly exterior wall thermal insulation porous material;

[0021] Preferably, in step S1, the amount of methyltrimethoxysilane added is 1.6-2.0 g. Methyltrimethoxysilane is both a hydrophobic modifier and a cross-linking agent, which is coated on the aerogel skeleton to make the connection between the fibers tighter, improve the mechanical properties and structural stability of the aerogel, and reduce the occurrence of pore collapse of cellulose aerogel. Methyltrimethoxysilane can generate a silicon dioxide carbon layer at high temperature, which can isolate heat and oxygen, thereby playing a flame retardant role.

[0022] The beneficial effects achieved by the present invention are as follows:

[0023] The present invention obtains a multi-dimensional pore-modified aerogel solution by modifying a flame-retardant pore-forming composite and methyltrimethoxysilane by a solution method, and further fills the pore structure of the aerogel with a gasified fly ash-based geopolymer filler, which not only increases the stability of the aerogel structure, but also increases the complexity of the pores, so that the pore structure of the material presents porosity, multi-dimensionality and multi-level properties, thereby significantly enhancing the thermal insulation performance, and at the same time having certain hydrophobic and flame-retardant properties, can play a waterproof and fireproof role, and enhances the applicability and durability of the exterior wall material; the multi- In the modified aerogel solution with 3D pores, polyvinyl alcohol and nanocellulose aerogel are modified with flame-retardant pore-forming composites and methyltrimethoxysilane. Methyltrimethoxysilane is used as a cross-linking agent and a hydrophobic modifier to coat the aerogel skeleton, which enhances the stability of the structure, reduces the risk of collapse of the cellulose aerogel, and makes it hydrophobic and flame-retardant. The flame-retardant pore-forming composite is then further cross-linked to enhance the uniformity and multi-level nature of pore formation, which can effectively capture and store energy, thereby enhancing the thermal insulation performance. The flame-retardant pore-forming composite is based on ZIF -8 zeolite imidazole framework material is evenly distributed on the surface of phosphorus-doped graphite-like nitrogen oxide, which not only reduces the agglomeration of ZIF-8 particles, but also introduces phosphorus, nitrogen and zinc elements, thereby improving the flame retardant and waterproof properties of the aerogel; in the gasified fly ash-based geopolymer filler, the gasified fly ash is modified to obtain a polysilicon-aluminum compound with a bonded network structure based on -SiO4-AlO4, which is then filled into a multidimensional pore-modified aerogel solution, which increases the surface pore structure and compressive strength of the aerogel, making the aerogel pore structure porous, The multidimensionality and multi-layered nature significantly enhances the thermal insulation, waterproof and flame retardant properties of the material. The gasified fly ash-based geopolymer filler can also be used as a stabilizer to reduce the collapse of pores in the aerogel, which is conducive to better exerting the thermal insulation, waterproof and fireproof properties. The present invention uses a flame-retardant pore-forming composite, a gasified fly ash-based geopolymer filler, nanocellulose, methyltrimethoxysilane and polyvinyl alcohol to make an environmentally friendly exterior wall thermal insulation porous material, which has excellent thermal insulation, fireproof and waterproof properties, and enhances the applicability, safety and durability of the exterior wall material. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a scanning electron microscope image of the environmentally friendly exterior wall thermal insulation porous material prepared in Example 1 of the present invention;

[0025] Figure 2 The thermal conductivity results of Examples 1-4 and Comparative Examples 1-3 of the present invention are shown in FIG.

[0026] Figure 3 The limiting oxygen index results of Examples 1-4 and Comparative Examples 1-3 of the present invention are shown in FIG.

[0027] Figure 4The contact angle results of Examples 1-4 and Comparative Examples 1-3 of the present invention are shown in FIG.

[0028] Figure 5 This is a scanning electron microscope image of the phosphorus-doped graphite-like nitrogen oxide prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0031] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0032] Example 1

[0033] This embodiment proposes an environmentally friendly exterior wall thermal insulation porous material, including the following components in parts by weight: 20 parts of a flame retardant pore-forming compound, 40 parts of a gasified fly ash-based geopolymer filler, 5 parts of nanocellulose, 10 parts of methyltrimethoxysilane, and 10 parts of polyvinyl alcohol.

[0034] The flame retardant pore-forming composite comprises the following components in parts by weight: 20 parts of phosphorus-doped graphite-like nitrogen oxide and 40 parts of ZIF-8 zeolite imidazole framework material.

[0035] The gasified fly ash-based geopolymer filler is a thermal insulation filler obtained by synergistically modifying the gasified fly ash as a raw material after calcination and activation, using sodium hydroxide, sodium silicate and deionized water to prepare an alkali activator, mixing and stirring the activated material, the alkali activator, the hydrogen peroxide foaming agent and the oleic acid foam stabilizer.

[0036] The preparation method of the flame retardant pore-forming composite material specifically comprises the following steps:

[0037] (1) Add urea and diammonium hydrogen phosphate to 300 mL of deionized water, the amount of urea added is 5.0 g, and magnetic stirring is performed for 4 hours at a stirring speed of 600 rpm to completely dissolve the urea. The amount of diammonium hydrogen phosphate added is 0.5 g. The addition of diammonium hydrogen phosphate provides phosphorus, which is beneficial to improving the flame retardant and waterproof properties of graphite-like nitrogen oxide. The clarified solution is placed in a refrigerator at -18°C for 12 hours, and then freeze-dried to remove moisture. The powder is added to a sealed ceramic crucible, and then calcined at 550°C for 4 hours in a muffle furnace. The heating time is controlled at 100 minutes. The yellow product is collected and ground. The phosphorus atom doping replaces the carbon sites in the graphite-like nitrogen oxide skeleton, and the basic morphology of the graphite-like nitrogen oxide is not destroyed. However, after phosphorus doping, the two-dimensional layered structure presents micron-sized wrinkles, and the nanosheets are larger and more obvious, thereby obtaining phosphorus-doped graphite-like nitrogen oxide;

[0038] (2) Pour 100 mg of zinc nitrate hexahydrate and the phosphorus-doped graphite-like nitrogen oxide described in step (1) into a methanol solution, disperse them by ultrasonication to form a uniform dispersion, then pour the dispersion into 10 mL of a methanol solution of 2-methylimidazole, wherein the methanol solution of 2-methylimidazole contains 1.2 g of 2-methylimidazole, stir at room temperature for 2 h, then allow to stand for precipitation, filter, wash, and dry, thereby forming a ZIF-8 zeolite imidazole framework material with zinc nitrate hexahydrate and 2-methylimidazole, wherein ZIF-8 particles are uniformly distributed on the surface of the phosphorus-doped graphite-like nitrogen oxide. And they are tightly combined to obtain a flame-retardant pore-forming composite, which not only reduces the agglomeration of ZIF-8 particles, but also is beneficial to the uniformity and multi-level pore-forming of the subsequent cross-linking reaction. The porous protective film of the composite itself also has certain flame-retardant and waterproof properties, which is beneficial to the safety and durability of the use of exterior wall building materials. The zinc atomic content in the flame-retardant pore-forming composite is 6.8%. The presence of zinc element has a good smoke suppression effect, and can be combined with phosphorus and nitrogen elements to exert more excellent flame-retardant properties. At the same time, zinc element can form an oxide protective film on the surface of the material, thus having good waterproof properties.

[0039] The preparation method of gasified fly ash-based geopolymer filler specifically comprises the following steps:

[0040] a. Put the gasified fly ash into a muffle furnace at 800°C and calcine until the mass no longer changes. Grind it. There are a large number of glass beads on the surface of the gasified fly ash particles. The main components are silicon dioxide and aluminum oxide. Under the action of high temperature, the originally stable and orderly structure is destroyed, and more amorphous monomers are generated, which is conducive to the alkali excitation reaction of the gasified fly ash and the leaching of silicon and aluminum elements in the fly ash, thereby preparing a polymer with higher strength, more uniformity and density, and obtaining a calcined activated material;

[0041] b. Mix sodium hydroxide, sodium silicate and 25 mL of deionized water and stir evenly. The amount of sodium hydroxide added is 2.0 g, and the amount of sodium silicate added is 6.5 g. Sodium silicate can effectively adjust the silicon-aluminum ratio in the reaction system, so as to facilitate the formation of uniform and stable bubble pores and good thermal insulation performance. Then weigh 30.0 g of the obtained alkali activator and the calcined activated material described in step a for mixing and stirring. Add 0.7 g of oleic acid foam stabilizer and 0.7 g of hydrogen peroxide foaming agent, stir rapidly for 2 min, stir at a speed of 1000 rpm, and a shear rate of 10000 rpm. Then pour the slurry into a mold and put it into a 60°C standard oven. After curing in a quasi-curing box for 3 days, under the action of sodium hydroxide, the covalent bonds of Si-O and Al-O in the gasified fly ash are broken, and reorganized and condensed to form a polysilicon-aluminum compound with a bonding network structure based on -SiO4-AlO4, which can increase the compressive strength of the polymer and form a large number of closed pores inside the geopolymer, effectively improving the porosity and enhancing the thermal insulation performance. Therefore, this process method is used to modify the gasified fly ash to prepare a geopolymer insulation material with fire resistance, high temperature resistance and high pressure resistance, which improves the current situation of easy aging of organic insulation materials and poor thermal insulation of inorganic materials, and obtains gasified fly ash-based geopolymer filler.

[0042] This embodiment provides a method for preparing an environmentally friendly exterior wall thermal insulation porous material, which specifically includes the following steps:

[0043] S1. Add 1.0 g of nanocellulose to 100 mL of deionized water, then add 2.0 g of polyvinyl alcohol, stir magnetically at room temperature for 24 h, add methyltrimethoxysilane liquid to the mixture of polyvinyl alcohol and nanocellulose, the amount of methyltrimethoxysilane added is 2.0 g, methyltrimethoxysilane is both a hydrophobic modifier and a cross-linking agent, and is coated on the aerogel skeleton to make the connection between the fibers tighter, improve the mechanical properties and structural stability of the aerogel, and reduce the occurrence of pore collapse of the cellulose aerogel. In addition, methyltrimethoxysilane A silicon dioxide carbon layer can be generated at high temperature. This carbon layer can isolate heat and oxygen, thus playing a flame retardant role. Stirring makes it evenly dispersed, then adding a flame retardant pore-forming composite, and magnetic stirring for 2 hours. Under the further cross-linking of the flame retardant pore-forming composite, the network structure of the aerogel is more dense, significantly enhancing the pore-forming uniformity and multi-level, and can effectively capture and store energy, and enhance the thermal insulation performance. In addition, the incorporation of phosphorus, nitrogen, and zinc elements in the flame retardant pore-forming composite improves the flame retardant and waterproof properties of the aerogel, and a multi-dimensional pore-modified aerogel solution is obtained;

[0044] S2. Pour the multidimensional pore modified aerogel solution described in step S1 into a silica gel mold, pre-freeze it in a refrigerator at 4°C for 2h, add the gasified fly ash-based geopolymer filler and stir it, then ultrasonically treat it for 2h, the ultrasonic temperature is 6°C, and the ultrasonic power is 800W, so that the gasified fly ash-based geopolymer filler can fully enter the pores of the aerogel, further fill the pore structure of the aerogel, provide the aerogel with abundant mesopores and increase the complexity of the pores, so that the micron-scale pore structure has porosity, multidimensionality and multi-level properties, thereby significantly enhancing the thermal insulation performance, waterproof performance and flame retardant performance. The mesh bonding structure of the gasified fly ash-based geopolymer filler also enhances the compressive strength of the aerogel, and can be used as a stabilizer to reduce the collapse of the pores in the aerogel, which is conducive to better exerting the thermal insulation, waterproof and fireproof properties, and improves the durability of the material. Then, vacuum freeze-drying is carried out at -70°C for 48h, and the obtained aerogel is placed in an oven at 80°C for 4h to obtain an environmentally friendly exterior wall thermal insulation porous material.

[0045] In this embodiment, the prepared environmentally friendly exterior wall thermal insulation porous material is subjected to a scanning electron microscope to observe its microscopic morphology. Figure 1 This is a SEM image of the environmentally friendly exterior wall thermal insulation porous material prepared in Example 1, magnified 400 times. Figure 1 The pore structure of the environmentally friendly exterior wall thermal insulation porous material prepared in this embodiment is dense and complex.

[0046] In this example, the prepared phosphorus-doped graphite-like nitrogen oxide was subjected to scanning electron microscopy to observe its microscopic morphology. Figure 5 This is a SEM image of the phosphorus-doped graphite-like nitrogen oxide prepared in Example 1, magnified 100,000 times. Figure 5 The phosphorus-doped graphite-like nitride oxide flakes prepared in this embodiment are larger and more obvious.

[0047] Example 2

[0048] This embodiment proposes an environmentally friendly exterior wall thermal insulation porous material, including the following components in parts by weight: 10 parts of a flame retardant pore-forming composite, 30 parts of a gasified fly ash-based geopolymer filler, 4 parts of nanocellulose, 8 parts of methyltrimethoxysilane, and 8 parts of polyvinyl alcohol.

[0049] The flame retardant pore-forming composite comprises the following components in parts by weight: 10 parts of phosphorus-doped graphite-like nitrogen oxide and 30 parts of ZIF-8 zeolite imidazole framework material.

[0050] The gasified fly ash-based geopolymer filler is a thermal insulation filler obtained by synergistically modifying the gasified fly ash as a raw material after calcination and activation, using sodium hydroxide, sodium silicate and deionized water to prepare an alkali activator, mixing and stirring the activated material, the alkali activator, the hydrogen peroxide foaming agent and the oleic acid foam stabilizer.

[0051] The preparation method of the flame retardant pore-forming composite material specifically comprises the following steps:

[0052] (1) Add urea and diammonium hydrogen phosphate to 200 mL of deionized water, the amount of urea added is 5.0 g, and magnetic stirring is performed for 3 hours at a stirring speed of 500 rpm to completely dissolve the urea. The amount of diammonium hydrogen phosphate added is 0.3 g. The addition of diammonium hydrogen phosphate provides phosphorus, which is beneficial to improving the flame retardant and waterproof properties of graphite-like nitrogen oxide. The clarified solution is placed in a refrigerator at -18°C for 10 hours, and then freeze-dried to remove moisture. The powder is added to a sealed ceramic crucible, and then calcined at 500°C for 3 hours in a muffle furnace. The heating time is controlled at 100 minutes. The yellow product is collected and ground. The phosphorus atom doping replaces the carbon sites in the graphite-like nitrogen oxide skeleton, and the basic morphology of the graphite-like nitrogen oxide is not destroyed. However, after phosphorus doping, the two-dimensional layered structure presents micron-sized wrinkles, and the nanosheets are larger and more obvious, thereby obtaining phosphorus-doped graphite-like nitrogen oxide;

[0053] (2) 80 mg of zinc nitrate hexahydrate and the phosphorus-doped graphite-like nitrogen oxide described in step (1) are poured into a methanol solution, ultrasonically dispersed to form a uniform dispersion, and then the dispersion is poured into 10 mL of a methanol solution of 2-methylimidazole, wherein the methanol solution of 2-methylimidazole contains 1.0 g of 2-methylimidazole, stirred at room temperature for 2 h, then allowed to stand for precipitation, filtered, washed, and dried to form a ZIF-8 zeolite imidazole framework material with zinc nitrate hexahydrate and 2-methylimidazole, wherein ZIF-8 particles are uniformly distributed on the surface of the phosphorus-doped graphite-like nitrogen oxide. And they are tightly combined to obtain a flame-retardant pore-forming composite, which not only reduces the agglomeration of ZIF-8 particles, but also is beneficial to the uniformity and multi-level pore-forming of the subsequent cross-linking reaction. The porous protective film of the composite itself also has certain flame-retardant and waterproof properties, which is beneficial to the safety and durability of the use of exterior wall building materials. The zinc atom content in the flame-retardant pore-forming composite is 5.4%. The presence of zinc element has a good smoke suppression effect, and can be combined with phosphorus and nitrogen elements to exert more excellent flame-retardant properties. At the same time, zinc element can form an oxide protective film on the surface of the material, thus having good waterproof properties.

[0054] The preparation method of gasified fly ash-based geopolymer filler specifically comprises the following steps:

[0055] a. Put the gasified fly ash into a muffle furnace at 700°C and calcine until the mass no longer changes. Grind it. There are a large number of glass beads on the surface of the gasified fly ash particles. The main components are silicon dioxide and aluminum oxide. Under the action of high temperature, the originally stable and orderly structure is destroyed, and more amorphous monomers are generated, which is conducive to the alkali excitation reaction of the gasified fly ash and the leaching of silicon and aluminum elements in the fly ash, thereby preparing a polymer with higher strength, more uniformity and density, and obtaining a calcined activated material;

[0056] b. Mix sodium hydroxide, sodium silicate and 25 mL of deionized water and stir evenly. The amount of sodium hydroxide added is 2.0 g, and the amount of sodium silicate added is 5.5 g. Sodium silicate can effectively adjust the silicon-aluminum ratio in the reaction system, which is conducive to the formation of uniform and stable bubble pores and has good thermal insulation performance. Then weigh 30.0 g of the obtained alkali activator and the calcined activated material described in step a for mixing and stirring, add 0.6 g of oleic acid foam stabilizer and 0.6 g of hydrogen peroxide foaming agent, stir rapidly for 1 min, stir at a speed of 800 rpm, and a shear rate of 8000 rpm. Then pour the slurry into a mold and put it into a 60°C standard After curing in a curing box for 3 days, under the action of sodium hydroxide, the covalent bonds of Si-O and Al-O in the gasified fly ash are broken, and reorganized and condensed to form a polysilicon-aluminum compound with a bonding network structure based on -SiO4-AlO4, which can increase the compressive strength of the polymer and form a large number of closed pores inside the geopolymer, effectively improving the porosity and enhancing the thermal insulation performance. Therefore, this process method is used to modify the gasified fly ash to prepare a geopolymer insulation material with fire resistance, high temperature resistance and high pressure resistance, which improves the current situation of easy aging of organic insulation materials and poor thermal insulation of inorganic materials, and obtains gasified fly ash-based geopolymer filler.

[0057] This embodiment provides a method for preparing an environmentally friendly exterior wall thermal insulation porous material, which specifically includes the following steps:

[0058] S1. Add 0.8 g of nanocellulose to 100 mL of deionized water, then add 1.6 g of polyvinyl alcohol, stir magnetically at room temperature for 24 h, add methyltrimethoxysilane liquid to the mixture of polyvinyl alcohol and nanocellulose, the amount of methyltrimethoxysilane added is 1.6 g, methyltrimethoxysilane is both a hydrophobic modifier and a cross-linking agent, and is coated on the aerogel skeleton to make the connection between the fibers tighter, improve the mechanical properties and structural stability of the aerogel, and reduce the occurrence of pore collapse of the cellulose aerogel. In addition, methyltrimethoxysilane A silicon dioxide carbon layer can be generated at high temperature. This carbon layer can isolate heat and oxygen, thus playing a flame retardant role. Stirring makes it evenly dispersed, then adding a flame retardant pore-forming composite, and magnetic stirring for 1 hour. Under the further cross-linking of the flame retardant pore-forming composite, the network structure of the aerogel is more dense, significantly enhancing the pore-forming uniformity and multi-level, and can effectively capture and store energy, and enhance the thermal insulation performance. In addition, the incorporation of phosphorus, nitrogen, and zinc elements in the flame retardant pore-forming composite improves the flame retardant and waterproof properties of the aerogel, and a multi-dimensional pore-modified aerogel solution is obtained;

[0059] S2. Pour the multidimensional pore modified aerogel solution described in step S1 into a silica gel mold, pre-freeze it in a refrigerator at 4°C for 1h, add the gasified fly ash-based geopolymer filler and stir it, then ultrasonically treat it for 1h, the ultrasonic temperature is 5°C, and the ultrasonic power is 600W, so that the gasified fly ash-based geopolymer filler can fully enter the pores of the aerogel, further fill the pore structure of the aerogel, provide the aerogel with abundant mesopores and increase the complexity of the pores, so that the micron-scale pore structure has porosity, multidimensionality and multi-level properties, thereby significantly enhancing the thermal insulation performance, waterproof performance and flame retardant performance. The network bonding structure of the gasified fly ash-based geopolymer filler also enhances the compressive strength of the aerogel, and can be used as a stabilizer to reduce the collapse of the pores in the aerogel, which is conducive to better exerting the thermal insulation, waterproof and fireproof properties, and improves the durability of the material. Then, vacuum freeze-drying is carried out at -70°C for 24h, and the obtained aerogel is placed in an oven at 70°C for 3h to obtain an environmentally friendly exterior wall thermal insulation porous material.

[0060] Example 3

[0061] This embodiment proposes an environmentally friendly exterior wall thermal insulation porous material, including the following components in parts by weight: 15 parts of a flame retardant pore-forming composite, 35 parts of a gasified fly ash-based geopolymer filler, 4.5 parts of nanocellulose, 9 parts of methyltrimethoxysilane, and 9 parts of polyvinyl alcohol.

[0062] The flame retardant pore-forming composite comprises the following components in parts by weight: 15 parts of phosphorus-doped graphite-like nitrogen oxide and 35 parts of ZIF-8 zeolite imidazole framework material.

[0063] The gasified fly ash-based geopolymer filler is a thermal insulation filler obtained by synergistically modifying the gasified fly ash as a raw material after calcination and activation, using sodium hydroxide, sodium silicate and deionized water to prepare an alkali activator, mixing and stirring the activated material, the alkali activator, the hydrogen peroxide foaming agent and the oleic acid foam stabilizer.

[0064] The preparation method of the flame retardant pore-forming composite material specifically comprises the following steps:

[0065] (1) Add urea and diammonium hydrogen phosphate to 250 mL of deionized water, the amount of urea added is 5.0 g, and magnetic stirring is performed for 3.5 hours at a stirring speed of 550 rpm to completely dissolve the urea. The amount of diammonium hydrogen phosphate added is 0.4 g. The addition of diammonium hydrogen phosphate provides phosphorus, which is beneficial to improving the flame retardant and waterproof properties of graphite-like nitrogen oxide. The clarified solution is placed in a refrigerator at -18°C for 11 hours, and then freeze-dried to remove moisture. The powder is added to a sealed ceramic crucible, and then calcined at 525°C for 3.5 hours in a muffle furnace. The heating time is controlled at 100 minutes. The yellow product is collected and ground. The phosphorus atom doping replaces the carbon sites in the graphite-like nitrogen oxide skeleton, and the basic morphology of the graphite-like nitrogen oxide is not destroyed. However, after phosphorus doping, the two-dimensional layered structure presents micron-sized wrinkles, and the nanosheets are larger and more obvious, thereby obtaining phosphorus-doped graphite-like nitrogen oxide;

[0066] (2) Pour 90 mg of zinc nitrate hexahydrate and the phosphorus-doped graphite-like nitrogen oxide described in step (1) into a methanol solution, disperse them by ultrasonication to form a uniform dispersion, then pour the dispersion into 10 mL of a 2-methylimidazole methanol solution, wherein the 2-methylimidazole methanol solution contains 1.1 g of 2-methylimidazole, stir at room temperature for 2 h, then allow to stand for precipitation, filter, wash, and dry, thereby forming a ZIF-8 zeolite imidazole framework material with zinc nitrate hexahydrate and 2-methylimidazole, wherein ZIF-8 particles are uniformly distributed on the surface of the phosphorus-doped graphite-like nitrogen oxide. And they are tightly combined to obtain a flame-retardant pore-forming composite, which not only reduces the agglomeration of ZIF-8 particles, but also is beneficial to the uniformity and multi-level pore-forming of the subsequent cross-linking reaction. The porous protective film of the composite itself also has certain flame-retardant and waterproof properties, which is beneficial to the safety and durability of the use of exterior wall building materials. The zinc atom content in the flame-retardant pore-forming composite is 6.1%. The presence of zinc element has a good smoke suppression effect, and can be combined with phosphorus and nitrogen elements to exert more excellent flame-retardant properties. At the same time, zinc element can form an oxide protective film on the surface of the material, thus having good waterproof properties.

[0067] The preparation method of gasified fly ash-based geopolymer filler specifically comprises the following steps:

[0068] a. Put the gasified fly ash into a muffle furnace at 750°C and calcine until the mass no longer changes. Grind it. There are a large number of glass beads on the surface of the gasified fly ash particles. The main components are silicon dioxide and aluminum oxide. Under the action of high temperature, the originally stable and orderly structure is destroyed, and more amorphous monomers are generated, which is conducive to the alkali excitation reaction of the gasified fly ash and the leaching of silicon and aluminum elements in the fly ash, thereby preparing a polymer with higher strength, more uniformity and density, and obtaining a calcined activated material;

[0069] b. Mix sodium hydroxide, sodium silicate and 25 mL of deionized water and stir evenly. The amount of sodium hydroxide added is 2.0 g, and the amount of sodium silicate added is 6.0 g. Sodium silicate can effectively adjust the silicon-aluminum ratio in the reaction system, which is conducive to the formation of uniform and stable bubble pores and has good thermal insulation performance. Then weigh 30.0 g of the obtained alkali activator and the calcined activated material described in step a for mixing and stirring, add 0.65 g of oleic acid foam stabilizer and 0.65 g of hydrogen peroxide foaming agent, stir rapidly for 1.5 min, stir at a speed of 900 rpm, and a shear rate of 9000 rpm. Then pour the slurry into a mold and put it into 60 ° C. After curing in a standard curing box for 3 days, under the action of sodium hydroxide, the Si-O and Al-O covalent bonds in the gasification fly ash are broken, and reorganized and condensed to form a polysilicon-aluminum compound with a bonded network structure based on -SiO4-AlO4, which can increase the compressive strength of the polymer and form a large number of closed pores inside the geopolymer, effectively improving the porosity and enhancing the thermal insulation performance. Therefore, this process method is used to modify the gasification fly ash to prepare a geopolymer insulation material with fire resistance, high temperature resistance and high pressure resistance, which improves the current situation of easy aging of organic insulation materials and poor thermal insulation of inorganic materials, and obtains gasification fly ash-based geopolymer filler.

[0070] This embodiment provides a method for preparing an environmentally friendly exterior wall thermal insulation porous material, which specifically includes the following steps:

[0071] S1. Add 0.9 g of nanocellulose to 100 mL of deionized water, then add 1.8 g of polyvinyl alcohol, stir magnetically at room temperature for 24 h, add methyltrimethoxysilane liquid to the mixture of polyvinyl alcohol and nanocellulose, the amount of methyltrimethoxysilane added is 1.8 g, methyltrimethoxysilane is both a hydrophobic modifier and a cross-linking agent, which is coated on the aerogel skeleton to make the connection between the fibers tighter, improve the mechanical properties and structural stability of the aerogel, and reduce the occurrence of pore collapse of the cellulose aerogel. In addition, methyltrimethoxysilane has a strong hydrophobic effect on the aerogel structure. A silicon dioxide carbon layer can be generated at high temperature. This carbon layer can isolate heat and oxygen, thus playing a flame retardant role. Stirring makes it evenly dispersed, then adding the flame retardant pore-forming composite, magnetic stirring for 1.5 hours, under the further cross-linking of the flame retardant pore-forming composite, the network structure of the aerogel is more dense, significantly enhancing the pore-forming uniformity and multi-level, can effectively capture and store energy, enhance the thermal insulation performance, and the incorporation of phosphorus, nitrogen, and zinc elements in the flame retardant pore-forming composite improves the flame retardant and waterproof properties of the aerogel, obtaining a multidimensional pore-modified aerogel solution;

[0072] S2, pour the multidimensional pore modified aerogel solution described in step S1 into a silica gel mold, pre-freeze it in a refrigerator at 4°C for 1.5 hours, add the gasified fly ash-based geopolymer filler and stir it, and then ultrasonically treat it for 1.5 hours, with an ultrasonic temperature of 5.5°C and an ultrasonic power of 700W, so that the gasified fly ash-based geopolymer filler can fully enter the pores of the aerogel and further fill the pore structure of the aerogel, providing the aerogel with abundant mesopores and increasing the complexity of the pores, so that the micron-scale pore structure has a porous The mesh bonding structure of the gasified fly ash-based geopolymer filler also enhances the compressive strength of the aerogel and can be used as a stabilizer to reduce the collapse of pores in the aerogel, which is conducive to better exerting the thermal insulation, waterproof and fireproof properties and improving the durability of the material. The aerogel is then vacuum freeze-dried at -70°C for 36 hours, and the obtained aerogel is placed in an oven at 75°C for 3.5 hours to obtain an environmentally friendly exterior wall thermal insulation porous material.

[0073] Example 4

[0074] This embodiment proposes an environmentally friendly exterior wall thermal insulation porous material, including the following components in parts by weight: 10 parts of a flame retardant pore-forming composite, 30 parts of a gasified fly ash-based geopolymer filler, 5 parts of nanocellulose, 8 parts of methyltrimethoxysilane, and 10 parts of polyvinyl alcohol.

[0075] The flame retardant pore-forming composite comprises the following components in parts by weight: 20 parts of phosphorus-doped graphite-like nitrogen oxide and 40 parts of ZIF-8 zeolite imidazole framework material.

[0076] The gasified fly ash-based geopolymer filler is a thermal insulation filler obtained by synergistically modifying the gasified fly ash as a raw material after calcination and activation, using sodium hydroxide, sodium silicate and deionized water to prepare an alkali activator, mixing and stirring the activated material, the alkali activator, the hydrogen peroxide foaming agent and the oleic acid foam stabilizer.

[0077] The preparation method of the flame retardant pore-forming composite material specifically comprises the following steps:

[0078] (1) Add urea and diammonium hydrogen phosphate to 300 mL of deionized water, the amount of urea added is 5.0 g, and magnetic stirring is performed for 3 hours at a stirring speed of 600 rpm to completely dissolve the urea. The amount of diammonium hydrogen phosphate added is 0.5 g. The addition of diammonium hydrogen phosphate provides phosphorus, which is beneficial to improving the flame retardant and waterproof properties of graphite-like nitrogen oxide. The clarified solution is placed in a refrigerator at -18°C for 10 hours, and then freeze-dried to remove moisture. The powder is added to a sealed ceramic crucible, and then calcined at 550°C for 3 hours in a muffle furnace. The heating time is controlled at 100 minutes. The yellow product is collected and ground. The phosphorus atom doping replaces the carbon sites in the graphite-like nitrogen oxide skeleton, and the basic morphology of the graphite-like nitrogen oxide is not destroyed. However, after phosphorus doping, the two-dimensional layered structure presents micron-sized wrinkles, and the nanosheets are larger and more obvious, thereby obtaining phosphorus-doped graphite-like nitrogen oxide;

[0079] (2) Pour 100 mg of zinc nitrate hexahydrate and the phosphorus-doped graphite-like nitrogen oxide described in step (1) into a methanol solution, disperse them by ultrasonication to form a uniform dispersion, then pour the dispersion into 10 mL of a methanol solution of 2-methylimidazole, wherein the methanol solution of 2-methylimidazole contains 1.2 g of 2-methylimidazole, stir at room temperature for 2 h, then allow to stand for precipitation, filter, wash, and dry, thereby forming a ZIF-8 zeolite imidazole framework material with zinc nitrate hexahydrate and 2-methylimidazole, wherein ZIF-8 particles are uniformly distributed on the surface of the phosphorus-doped graphite-like nitrogen oxide. And they are tightly combined to obtain a flame-retardant pore-forming composite, which not only reduces the agglomeration of ZIF-8 particles, but also is beneficial to the uniformity and multi-level pore-forming of the subsequent cross-linking reaction. The porous protective film of the composite itself also has certain flame-retardant and waterproof properties, which is beneficial to the safety and durability of the use of exterior wall building materials. The zinc atomic content in the flame-retardant pore-forming composite is 6.8%. The presence of zinc element has a good smoke suppression effect, and can be combined with phosphorus and nitrogen elements to exert more excellent flame-retardant properties. At the same time, zinc element can form an oxide protective film on the surface of the material, thus having good waterproof properties.

[0080] The preparation method of gasified fly ash-based geopolymer filler specifically comprises the following steps:

[0081] a. Put the gasified fly ash into a muffle furnace at 800°C and calcine until the mass no longer changes. Grind it. There are a large number of glass beads on the surface of the gasified fly ash particles. The main components are silicon dioxide and aluminum oxide. Under the action of high temperature, the originally stable and orderly structure is destroyed, and more amorphous monomers are generated, which is conducive to the alkali excitation reaction of the gasified fly ash and the leaching of silicon and aluminum elements in the fly ash, thereby preparing a polymer with higher strength, more uniformity and density, and obtaining a calcined activated material;

[0082] b. Mix sodium hydroxide, sodium silicate and 25 mL of deionized water and stir evenly. The amount of sodium hydroxide added is 2.0 g, and the amount of sodium silicate added is 6.5 g. Sodium silicate can effectively adjust the silicon-aluminum ratio in the reaction system, so as to facilitate the formation of uniform and stable bubble pores and good thermal insulation performance. Then weigh 30.0 g of the obtained alkali activator and the calcined activated material described in step a for mixing and stirring. Add 0.7 g of oleic acid foam stabilizer and 0.7 g of hydrogen peroxide foaming agent, stir rapidly for 1 min, stir at a speed of 1000 rpm, and a shear rate of 10000 rpm. Then pour the slurry into a mold and put it into a 60°C standard oven. After curing in a quasi-curing box for 3 days, under the action of sodium hydroxide, the covalent bonds of Si-O and Al-O in the gasified fly ash are broken, and reorganized and condensed to form a polysilicon-aluminum compound with a bonding network structure based on -SiO4-AlO4, which can increase the compressive strength of the polymer and form a large number of closed pores inside the geopolymer, effectively improving the porosity and enhancing the thermal insulation performance. Therefore, this process method is used to modify the gasified fly ash to prepare a geopolymer insulation material with fire resistance, high temperature resistance and high pressure resistance, which improves the current situation of easy aging of organic insulation materials and poor thermal insulation of inorganic materials, and obtains gasified fly ash-based geopolymer filler.

[0083] This embodiment provides a method for preparing an environmentally friendly exterior wall thermal insulation porous material, which specifically includes the following steps:

[0084] S1. Add 1.0 g of nanocellulose to 100 mL of deionized water, then add 2.0 g of polyvinyl alcohol, stir magnetically at room temperature for 24 h, add methyltrimethoxysilane liquid to the mixture of polyvinyl alcohol and nanocellulose, the amount of methyltrimethoxysilane added is 1.6 g, methyltrimethoxysilane is both a hydrophobic modifier and a cross-linking agent, and is coated on the aerogel skeleton to make the connection between the fibers tighter, improve the mechanical properties and structural stability of the aerogel, and reduce the occurrence of pore collapse of the cellulose aerogel. A silicon dioxide carbon layer can be generated at high temperature. This carbon layer can isolate heat and oxygen, thus playing a flame retardant role. Stirring makes it evenly dispersed, then adding a flame retardant pore-forming composite, and magnetic stirring for 1 hour. Under the further cross-linking of the flame retardant pore-forming composite, the network structure of the aerogel is more dense, significantly enhancing the pore-forming uniformity and multi-level, and can effectively capture and store energy, and enhance the thermal insulation performance. In addition, the incorporation of phosphorus, nitrogen, and zinc elements in the flame retardant pore-forming composite improves the flame retardant and waterproof properties of the aerogel, and a multi-dimensional pore-modified aerogel solution is obtained;

[0085] S2. Pour the multidimensional pore modified aerogel solution described in step S1 into a silica gel mold, pre-freeze it in a refrigerator at 4°C for 1h, add the gasified fly ash-based geopolymer filler and stir it, then ultrasonically treat it for 1h, the ultrasonic temperature is 6°C, and the ultrasonic power is 800W, so that the gasified fly ash-based geopolymer filler can fully enter the pores of the aerogel, further fill the pore structure of the aerogel, provide the aerogel with abundant mesopores and increase the complexity of the pores, so that the micron-scale pore structure has porosity, multidimensionality and multi-level properties, thereby significantly enhancing the thermal insulation performance, waterproof performance and flame retardant performance. The mesh bonding structure of the gasified fly ash-based geopolymer filler also enhances the compressive strength of the aerogel, and can be used as a stabilizer to reduce the collapse of the pores in the aerogel, which is conducive to better exerting the thermal insulation, waterproof and fireproof properties, and improves the durability of the material. Then, vacuum freeze-drying is carried out at -70°C for 24h, and the obtained aerogel is placed in an oven at 80°C for 3h to obtain an environmentally friendly exterior wall thermal insulation porous material.

[0086] Comparative Example 1

[0087] This comparative example provides an environmentally friendly exterior wall thermal insulation porous material, which differs from Example 1 in that the flame retardant pore-forming composite does not contain phosphorus-doped graphite-like nitrogen oxide; the preparation method of the flame retardant pore-forming composite does not include step (1); the preparation method of the gasified fly ash-based geopolymer filler is the same as that of Example 1; and the preparation method of the environmentally friendly exterior wall thermal insulation porous material is the same as that of Example 1.

[0088] Comparative Example 2

[0089] This comparative example provides an environmentally friendly exterior wall thermal insulation porous material, which differs from Example 1 in that the gasified fly ash in the gasified fly ash-based geopolymer filler is not calcined and activated; the preparation method of the flame-retardant pore-forming composite is the same as that of Example 1; the preparation method of the gasified fly ash-based geopolymer filler does not include step a; the preparation method of the environmentally friendly exterior wall thermal insulation porous material is the same as that of Example 1.

[0090] Comparative Example 3

[0091] This comparative example provides an environmentally friendly exterior wall thermal insulation porous material, which differs from Example 1 in that the multidimensional pore modified aerogel solution does not contain methyltrimethoxysilane; the preparation method of the flame retardant pore-forming composite is the same as that of Example 1; the preparation method of the gasified fly ash-based geopolymer filler is the same as that of Example 1; in the preparation method S1 of the environmentally friendly exterior wall thermal insulation porous material, methyltrimethoxysilane liquid is not added to the mixed solution of polyvinyl alcohol and nanocellulose.

[0092] Experimental Example 1

[0093] Thermal insulation performance test

[0094] Test sample: the environmentally friendly exterior wall thermal insulation porous material prepared in Examples 1-4 and Comparative Examples 1-3.

[0095] Test method: Use Tci thermal conductivity tester to measure the thermal conductivity (mW·m −1 ·K −1 ) was tested in accordance with ISO22007-2.2. The test method was transient flat plate heat source method (TPS). Under normal temperature and pressure conditions, 3 parallel specimens were tested for each sample, and the results were averaged. The smaller the thermal conductivity, the better the thermal insulation performance.

[0096] Figure 2 The thermal conductivity results of Examples 1-4 and Comparative Examples 1-3 are shown in FIG. As shown in the figure, the thermal conductivity of Examples 1-4 is 33.1-34.8 mW·m −1 ·K −1 , indicating good thermal insulation performance; the thermal conductivity of comparative examples 1-3 is 42.5-48.9mW·m −1 ·K −1 , indicating that the thermal insulation performance is poor; the flame-retardant pore-forming composite of comparative example 1 does not contain phosphorus-doped graphite-like nitrogen oxide, which cannot reduce the agglomeration of ZIF-8 particles, is not conducive to the uniformity and hierarchy of pore formation, and results in poor thermal insulation performance; the gasified fly ash-based geopolymer filler of comparative example 2 does not perform calcination activation on the gasified fly ash, and cannot better leach the silicon and aluminum elements in the fly ash, which is not conducive to the alkali excitation reaction of the gasified fly ash, and is not conducive to the formation of a uniform and dense polymer, resulting in poor thermal insulation performance; the multidimensional pore-modified aerogel solution of comparative example 3 does not contain methyltrimethoxysilane, and cannot play the role of a cross-linking agent, which is not conducive to the stability of the aerogel structure, nor is it conducive to further cross-linking reactions, which weakens the complexity of the pores and results in poor thermal insulation performance.

[0097] Experimental Example 2

[0098] Flame retardant performance test

[0099] Test sample: the environmentally friendly exterior wall thermal insulation porous material prepared in Examples 1-4 and Comparative Examples 1-3.

[0100] Test method: Use JF-5 limiting oxygen index tester to measure the limiting oxygen index (LOI) of the test sample. Test according to GB / T8924-2005. Test 5 samples in each group and take the average value of the results. The larger the limiting oxygen index, the stronger the flame retardant performance.

[0101] Figure 3The limiting oxygen index result diagram of Examples 1-4 and Comparative Examples 1-3 is shown in the figure; as shown in the figure, the limiting oxygen index of Examples 1-4 is 40.3-42.1%, indicating that the flame retardant performance is strong; the limiting oxygen index of Comparative Examples 1-3 is 31.8-37.6%, indicating that the flame retardant performance is weak; the flame retardant pore-forming composite of Comparative Example 1 does not contain phosphorus-doped graphite-like nitrogen oxide, and phosphorus and nitrogen elements cannot be introduced to play a flame retardant role, and it is not conducive to the uniform dispersion of ZIF-8, which limits the ZIF-8 zeolite imidazole framework material. Flame retardancy, resulting in weak flame retardancy; the gasified fly ash-based geopolymer filler in Comparative Example 2 does not undergo calcination activation, which is not conducive to the formation of a polysilicon-aluminum compound with a bonded network structure, and cannot better fill the pore structure of the aerogel, which is not conducive to increasing the complexity of the pores, resulting in weak flame retardancy; the multidimensional pore-modified aerogel solution in Comparative Example 3 does not contain methyltrimethoxysilane, which can neither exert its own flame retardant effect nor improve the stability and porosity of the aerogel structure, resulting in weak flame retardancy.

[0102] Experimental Example 3

[0103] Waterproof performance test

[0104] Test sample: the environmentally friendly exterior wall thermal insulation porous material prepared in Examples 1-4 and Comparative Examples 1-3.

[0105] Test method: The water contact angle of the test sample is measured using an OCA15EC contact angle tester. A 5μL water droplet is deposited on the sample surface using the solid drop method. The droplets are photographed horizontally from four directions. The surface water contact angle is measured in parallel three times, and the average value is taken. The larger the contact angle, the better the waterproof performance.

[0106] Figure 4 The contact angle results of Examples 1-4 and Comparative Examples 1-3 are shown in the figure; as shown in the figure, the contact angle of Examples 1-4 is 135.3-138.2°, indicating that the waterproof performance is better; the contact angle of Comparative Examples 1-3 is 116.5-124.7°, indicating that the waterproof performance is average; the flame retardant pore-forming composite of Comparative Example 1 does not contain phosphorus-doped graphite-like nitrogen oxide, which cannot isolate moisture through the wrinkled nanosheet structure, and is not conducive to the hydrophobicity of the ZIF-8 zeolite imidazole framework material, resulting in average waterproof performance; the gasified fly ash of Comparative Example 2 Failure to calcinate and activate the gasified fly ash in the base geological polymer filler is not conducive to the formation of a polymer with a bonded network structure, so that the aerogel pore structure cannot be porous, multidimensional and multi-layered, which weakens the barrier to moisture and results in average waterproof performance; the multidimensional pore modified aerogel solution of comparative example 3 does not contain methyltrimethoxysilane, and cannot perform hydrophobic modification on polyvinyl alcohol and nanocellulose aerogel, which is not conducive to the stability and porosity of the aerogel structure, thereby limiting the barrier to moisture and resulting in average waterproof performance.

[0107] The above experimental results show that the thermal insulation performance, flame retardant performance and waterproof performance of Examples 1-4 of the present invention are significantly better than those of Comparative Examples 1-3. Among them, Example 1 using a flame retardant pore-forming composite and a gasified fly ash-based geopolymer filler has better thermal insulation performance, stronger flame retardant performance and better waterproof performance. The polyvinyl alcohol and nanocellulose aerogel are modified with a flame retardant pore-forming composite and methyltrimethoxysilane. Methyltrimethoxysilane is used as a cross-linking agent and a hydrophobic modifier to coat the aerogel skeleton, which enhances the stability of the structure and makes it hydrophobic and flame retardant. Then the flame retardant pore-forming composite is used. Further cross-linking enhances the uniformity and multi-level nature of pore formation, can effectively capture and store energy, and enhance thermal insulation performance. The gasified fly ash is modified to obtain a polysilicon-aluminum compound with a bonded network structure based on -SiO4-AlO4, which is then filled into a multidimensional pore-modified aerogel solution, which increases the surface pore structure and compressive strength of the aerogel, making the aerogel pore structure porous, multidimensional and multi-level. The gasified fly ash-based geopolymer filler can also be used as a stabilizer to reduce the collapse of pores in the aerogel, significantly enhancing the thermal insulation, waterproof and flame retardant properties of the material.

[0108] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

[0109] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. An environmentally friendly exterior wall thermal insulation porous material, characterized by: The environmentally friendly exterior wall thermal insulation porous material comprises the following components in parts by weight: 10-20 parts of a flame retardant pore-forming compound, 30-40 parts of a gasified fly ash-based geopolymer filler, 4-5 parts of nanocellulose, 8-10 parts of methyltrimethoxysilane, and 8-10 parts of polyvinyl alcohol; the flame retardant pore-forming compound comprises the following components in parts by weight: 10-20 parts of phosphorus-doped graphite-like nitrogen oxide, and 30-40 parts of a ZIF-8 zeolite imidazole framework material; the gasified fly ash-based geopolymer filler is a thermal insulation filler obtained by calcining and activating gasified fly ash as a raw material, using sodium hydroxide, sodium silicate and deionized water to form an alkali activator, mixing and stirring the activated material, the alkali activator, a hydrogen peroxide foaming agent and an oleic acid foam stabilizer, and synergistically modifying the material.

2. A method for preparing the environmentally friendly exterior wall thermal insulation porous material according to claim 1, characterized in that: The specific steps include: S1. Add 0.8-1.0 g of nanocellulose to 100 mL of deionized water, then add 1.6-2.0 g of polyvinyl alcohol, and stir magnetically at room temperature for 24 h. Add methyltrimethoxysilane liquid to the mixture of polyvinyl alcohol and nanocellulose, stir to make it evenly dispersed, then add the flame-retardant pore-forming composite, and stir magnetically for 1-2 h to obtain a multidimensional pore-modified aerogel solution. S2. Pour the multidimensional pore modified aerogel solution described in step S1 into a silica gel mold, pre-freeze it in a refrigerator at 4°C for 1-2h, add gasified fly ash-based geopolymer filler and stir it, then ultrasonically treat it for 1-2h, the ultrasonic temperature is 5-6°C, the ultrasonic power is 600-800W, and then vacuum freeze-dried at -70°C for 24-48h. The obtained aerogel is placed in an oven at 70-80°C and dried for 3-4h to obtain an environmentally friendly exterior wall thermal insulation porous material.

3. The method for preparing the environmentally friendly exterior wall thermal insulation porous material according to claim 2, characterized in that: In step S1, the amount of methyltrimethoxysilane added is 1.6-2.0 g.

4. The method for preparing the environmentally friendly exterior wall thermal insulation porous material according to claim 3, characterized in that: The method for preparing the flame-retardant pore-forming composite specifically comprises the following steps: (1) adding urea and diammonium hydrogen phosphate to 200-300 mL of deionized water, the amount of urea added being 5.0 g, and magnetically stirring for 3-4 hours at a stirring speed of 500-600 rpm to completely dissolve the urea. The clarified solution is placed in a refrigerator at -18°C for 10-12 hours, and then freeze-dried to remove moisture. The solution is ground into powder and added to a sealed ceramic crucible. The solution is then calcined in a muffle furnace at 500-550°C for 3-4 hours, with the heating time controlled within 100 minutes. The yellow product is collected and ground to obtain phosphorus-doped graphite-like nitrogen oxide. (2) Pour 80-100 mg of zinc nitrate hexahydrate and the phosphorus-doped graphite-like nitrogen oxide described in step (1) into a methanol solution, disperse them by ultrasonication to form a uniform dispersion, then pour the dispersion into 10 mL of a 2-methylimidazole methanol solution containing 1.0-1.2 g of 2-methylimidazole, stir at room temperature for 2 h, then allow to stand and precipitate, filter, wash, and dry to obtain a flame-retardant pore-forming composite.

5. The method for preparing the environmentally friendly exterior wall thermal insulation porous material according to claim 4, characterized in that: In step (1), the amount of diammonium hydrogen phosphate added is 0.3-0.5 g.

6. The method for preparing the environmentally friendly exterior wall thermal insulation porous material according to claim 5, characterized in that: In step (2), the content of zinc atoms in the flame retardant pore-forming composite is 5.4-6.8%.

7. The method for preparing the environmentally friendly exterior wall thermal insulation porous material according to claim 6, characterized in that: The method for preparing the gasified fly ash-based geopolymer filler specifically comprises the following steps: a. Place the gasified fly ash in a muffle furnace at 700-800°C and calcine until the mass no longer changes, then grind to obtain a calcined activated material; b. Mix sodium hydroxide and sodium silicate with 25 mL of deionized water and stir evenly. The amount of sodium hydroxide added is 2.0 g. Then weigh 30.0 g of the obtained alkali activator and the calcined activated material described in step a and mix and stir. Add 0.6-0.7 g of oleic acid foam stabilizer and 0.6-0.7 g of hydrogen peroxide foaming agent. Stir rapidly for 1-2 min at a stirring speed of 800-1000 rpm and a shear rate of 8000-10000 rpm. Then pour the slurry into a mold and put it into a standard curing box at 60° C. for curing for 3 days to obtain a gasified fly ash-based geopolymer filler.

8. The method for preparing the environmentally friendly exterior wall thermal insulation porous material according to claim 7, characterized in that: In step b, the amount of sodium silicate added is 5.5-6.5 g.

Citation Information

Patent Citations

  • Preparation method of hydrophobic nano cellulose aerogel

    CN105622767A

  • Graphite-like carbon nitride / graphene / graphene oxide composite aerogel and preparation method thereof

    CN113617351A

  • Phosphorus-doped high-activity graphite-like carbon nitride nanosheet and method

    CN114602523A

  • Method for preparing foaming geopolymer from waste incineration fly ash

    CN116375493A

  • Dry particulate compositions for the formation of geopolymers, a process for forming geopolymers and the geopolymers obtained as a result

    WO2018024474A1